CARLo‐5 as an oncogenic gene in endometrial carcinoma. (18th November 2019) - Zhao, Xiwa; Zhang, Cong; Wei, Xurui; Shi, Li; Dai, Suli; Jia, Jingde; Wei, Sisi; Wang, Yaojie; Wang, Yanxiu; Cheng, Jianxin; Zhao, Lianmei
Abstract : The long noncoding RNA CARLo‐5 is dysregulated in multiple types of human cancers. High CARLo‐5 is a promising predictive factor for various cancers, including endometrial carcinoma (EC). Our previous study showed that the expression level of CARLo‐5 was associated with advanced FIGO stage (The International Federation of Gynecology and Obstetrics), lymph node metastasis, and the poor survival of patients with EC. In the present study, we demonstrated that the downregulation of CARLo‐5 could affect the proliferation, cell cycle, migration, and invasion of EC cell lines HEC‐1B and KLE cells. The oncogenic activity of CARLo‐5 was also confirmed with in vivo data. Mechanistically, CARLo‐5 could affect the expression of CDK/CDKN1A and MMP2/9, which have been reported to be regulated by CARLo‐5 and associated with cell cycle and motility. In conclusion, this study is the first to discover the biological function and mechanism of CARLo‐5 in regulating the biological characteristics of EC cells. Targeting CARLo‐5 and its pathway might provide new biomarkers or potential therapies target for patients with EC. Environ. Mol. Mutagen. 61:256–265, 2020. © 2019 Wiley Periodicals, Inc.